2021
DOI: 10.1186/s12910-021-00715-2
|View full text |Cite
|
Sign up to set email alerts
|

Governance frameworks for COVID-19 research ethics review and oversight in Latin America: an exploratory study

Abstract: Background Research has been an essential part of the COVID-19 pandemic response, including in Latin American (LA) countries. However, implementing research in emergency settings poses the challenge of producing valuable knowledge rapidly while upholding research ethical standards. Research ethics committees (RECs) therefore must conduct timely and rigorous ethics reviews and oversight of COVID-19 research. In the LA region, there is limited knowledge on how countries have responded to this nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
(23 reference statements)
0
15
0
1
Order By: Relevance
“…In the African context, research also often takes place in the context of historical inequities and ongoing power imbalances. People who are most disadvantaged or vulnerable, through poverty, marginalisation, or lack of access to healthcare are often disproportionately affected [ 4 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the African context, research also often takes place in the context of historical inequities and ongoing power imbalances. People who are most disadvantaged or vulnerable, through poverty, marginalisation, or lack of access to healthcare are often disproportionately affected [ 4 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CA-DR region has significant potential for developing strong and solid mechanisms for sharing experiences to improve research ethics governance. This potential is evident in examples of progress across the different countries in the region in terms of regulatory frameworks, prioritization of initiatives, funding, ethics committee networks, ethics committee training and community representation in research [ 16 , 22 – 24 ]. The GoEtiCA participatory action research project allowed a broad audience to meet virtually and provide insight, experiences and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of the Council for International Organizations of Medical Sciences (CIOMS) Ethical Guideline 20 on Research in Disaster and Disease Outbreak Situations [ 18 ], implementation of operating procedures based on this guideline has been limited. Palmero et al [ 22 ] concluded that “[c]ontinuing efforts should be directed to strengthen [Latin American] countries’ research capacity to respond timely and ethically to future health emergencies”. In this study we confirm that there is a clear need to improve ethics review practices in light of the difficulties identified by study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The CA-DR region has signi cant potential for developing strong and solid for sharing experiences to improve ethical governance. This potential can be seen in examples of progress across the different countries in the region in terms of regulatory frameworks, prioritization of initiatives, funding, ethics committee networks, ethics committee training, and community representation in research (13,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, research ethics structures have not been studied consistently, evidenced by a scarcity of publications on the topic across Central American countries. More recently, research priorities for the COVID-19 pandemic were identi ed with participants from various countries; however, the Central American response to these recommendations is unclear (13,14,15). Scienti c development, collaboration, and cooperation mechanisms among research stakeholders are urgently needed to promote the full adoption of international research ethics standards.…”
Section: Introductionmentioning
confidence: 99%